Epidemiology in Latin America: an opportunity for a global dialogue. - Pearce N (B M J PUBLISHING GROUP, 2008)
None
Editorial
Keywords: Epidemiology; Latin America; Public health; Fields of Research::320000 Medical and Health Sciences::321200 Public Health and Health Services::321202 Epidemiology